The Effect of Financial Literacy on Impulsive Buying Behavior Towards Online Food Delivery of Generation Z and Millennials in Indonesia with Media as A Moderating Variable - Oktaviana, Yasinta; Irawan, Atika (Integrasi Sains Media, 2024)
The rapid growth of online food delivery applications (OFDA), coupled with the increasing digital media exposure of younger generations, has raised concerns about impulsive buying behavior and its financial implications. This study investigates the effect of financial literacy on impulsive buying behavior towards OFDA among Generation Z and Millennials in Indonesia, with media as a moderating variable. This study employed a quantitative approach. The object of this study is Generation Z, aged 17-27 years old, and Millennials, aged 28-43 years old, living in Indonesia. The number of participants includes 434 for Generation Z and 407 for Millennials. The research uses Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) to examine the relationships between variables and compare effects across generational groups. The findings reveal that financial literacy positively and significantly affects impulsive buying behavior towards OFDA in the entire group, Generation Z and Millennials. The effect is stronger in Generation Z than in the complete and Millennial groups. The study also found a significant moderating effect of media usage, highlighting the importance of considering digital influences in financial behavior research. Based on these findings, the study recommends further research to explore the underlying factors causing this positive relationship. For practical applications for individuals, the study suggests that Generation Z and Millennials should implement their financial knowledge more effectively to manage their finances and distinguish between essential and non-essential spending. The study suggests incorporating financial literacy into curricula through courses and practical programs for educational institutions. The study suggests leveraging digital platforms for government bodies to provide interactive financial literacy content. This research significantly advances the understanding of financial literacy's impact on consumer behavior in the digital age, particularly in the context of OFDA among younger generations in Indonesia; by including media usage as a moderating variable, the research explores how digital media exposure influences the relationship between financial literacy and impulsive buying behavior. This aspect of the study underscores the media's significant role in shaping financial behaviors in the digital age.